(untitled) (Fiep Bulletin - online, 2014)
The importance of the physical aptitude level of the life-guards comes in result of the responsibility which is given to them, the life of human beings. The study identified the physical and functional conditions of the civil life-guards from the city of Balneário Arroio do Silva that had worked in the summering operation of 2005/2006. The sample of the study was constituted by 9 civil life-guards, with ages between 18 to 25 years, male people, chosen by chance. The data collection was carried through in Golden Park sporting complex, which is located in the general road that leads to Balneário Arroio do Silva. The assessment included the following information: a) personal data; b) anthropometric evaluation; c) functional evaluation; d) motor evaluation. It can be observed in the analysis of the final data which really express the reality of the life-guards. The corporal weight of the life-guards had a reduction of 2,43 kg in average; the Corporal Mass Table (CMT) had a 0,76% reduction; these results follow in the fat percentage, with a reduction of 2,01% of fat; the flexibility level was practically remained in the pre and post test; in the bar test, it had a reduction of one repetition; the abdominal test had the increase in the number of repetitions of 0,33 in average; in the 50 meters test the individuals had an increase of 0,11 seconds; in the 2.400 meters test, it had a reduction in the time of 0,61 seconds; in the 500 meters swimming test, it had a time improvement of 0,25 seconds. It is evident in this work that some physical qualities had been improved, rather due to their professional activity than to their preparatory training for the exercise of professional activity.